2010
DOI: 10.1002/met.201
|View full text |Cite
|
Sign up to set email alerts
|

Emergency manager decision‐making and tornado warning communication

Abstract: Emergency managers (EMs) play a critical role in communicating severe weather and tornado warnings to the public, yet communicating the uncertainty of when, where or if a tornado may hit remains a great challenge for EMs. Focus group and survey data concerning weather product usage, weather observing spotter interaction, and decisions to warn the public were collected from Oklahoma EMs in order to characterize the communication processes EMs employ during severe weather outbreaks. These processes include: (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Hammer and Schmidlin (2002) found that human response to tornado warnings is also contingent on such factors as warning lead times and availability of transportation or shelters. When identifying improvement opportunities for future warning dissemination and risk communication, some researchers have underscored the importance of coupling advances in technology with an understanding of human sociology and psychology vis-à-vis tornado events (Ashley, 2007;League et al, 2010). To illustrate, efforts to Physical Geography adopt fine-grained data to reduce uncertainty (League et al, 2010) or a new model to give forecasters credit for close calls to increase warning credibility should parallel efforts to educate the public about tornado path directions or the dangers of using highway overpasses as shelter (Schmidlin et al, 2009;Sherman-Morris, 2010;Suckling & Ashley, 2006).…”
Section: Tornadoesmentioning
confidence: 99%
“…Hammer and Schmidlin (2002) found that human response to tornado warnings is also contingent on such factors as warning lead times and availability of transportation or shelters. When identifying improvement opportunities for future warning dissemination and risk communication, some researchers have underscored the importance of coupling advances in technology with an understanding of human sociology and psychology vis-à-vis tornado events (Ashley, 2007;League et al, 2010). To illustrate, efforts to Physical Geography adopt fine-grained data to reduce uncertainty (League et al, 2010) or a new model to give forecasters credit for close calls to increase warning credibility should parallel efforts to educate the public about tornado path directions or the dangers of using highway overpasses as shelter (Schmidlin et al, 2009;Sherman-Morris, 2010;Suckling & Ashley, 2006).…”
Section: Tornadoesmentioning
confidence: 99%
“…Official messages need to be specific, consistent, clear, and accurate and should also include explicit conclusions about the threat. Several studies have also indicated that information is regarded more trustworthy if the source is located in the same social network, for instance neighbours, family, and friends, especially when compared to information coming through media (Crowe, 2010;Earle et al, 2010;Elliott & Pais, 2006;Friese, 2009;Gregg et al, 2007;Jalarajan Raj et al, 2010;Landau, 2011;League et al, 2010;Merchant et al, 2011;Mersham, 2010;Molinari & Handmer, 2011;Nakatani, Suzuki, Sakata, & Nishida, 2009;Samarajiva, 2005;Saylor, Cowart, Lipovsky, Jackson, & Finch, Jr., 2003;Sutton, 2009;Tekeli-Yes ßil et al, 2010;Veil et al, 2011;Voorhees, Vick, & Perkins, 2007;Wang & Li, 2008;Wei, Zhao, Yang, Du, & Marinova, 2010;Yates & Paquette, 2011).…”
Section: Responses and Reactions To Crisis Informationmentioning
confidence: 99%
“…Timely response is also an important evaluation factor when planning for using social media within emergency management organizations (Earle et al, 2010;Landau, 2011;League et al, 2010;Samarajiva, 2005;Wei et al, 2010).…”
Section: Warning Componentsmentioning
confidence: 99%
See 2 more Smart Citations